Design of an Android-based Troubled Gas Detection Tool Report Application at PT. Saka Tunggal Mandiri Jaya - Din Nuryanto; Kusuma, Susanna Dwi Yulianti (Information Technology and Science (ITScience), 2024)
Inspections are carried out to check objects to ensure that they meet certain standards. Laboratory officers have difficulty in the reporting process requested by the head of the section quickly, because officers must compare all gas detection device data. And laboratory officers sometimes leave the completeness of other supporting devices. So that each equipment officer has difficulty determining which units are damaged or repaired. Application research methods include literature study analysis, interviews, observations, while the development method used is the waterfall model. The design of the application displayed uses the android platform, the software used in building the application is android studio with the java programming language, while MySQL as a database. The purpose of this research is to provide information needed by PT Saka Tunggal Manadiri Jaya in improving product quality. The results achieved at the end of the study are the application of the gas detection device problem report in providing characteristic inspection information, making it easier for users to obtain inspection report information searches along with product items produced in accordance with the provisions and standards of inspection control of one very important component. By utilizing android-based technology through mobile devices. In order to find out the types of inspections in quality control either functional or tool change.